2014
DOI: 10.5114/ceji.2014.42122
|View full text |Cite
|
Sign up to set email alerts
|

Purification of pituitary autoantigen by column liquid chromatography and chromatofocusing

Abstract: IntroductionPituitary autoantibodies can be determined both in patients with pituitary disease as well as patients with autoimmune endocrine diseases. The purpose of the study was to isolate and purify pituitary autoantigen using sera of patients and the microsomal fraction of the pituitary.Material and methodsTo isolate a pituitary autoantigen, patient sera were used, which showed a strong immune response to pituitary antigens. Pituitary microsomal fractions were prepared from pituitary tissue homogenates. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Finally, Sawicka et al . [31-33] observed that the incidence of pituitary antibodies in autoimmune endocrine diseases was 41% and that these antibodies react mostly with an autoantigen weighing 68 kDa. Despite the number of studies conducted so far, only a few pituitary autoantigens responsible for the autoimmune processes have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Sawicka et al . [31-33] observed that the incidence of pituitary antibodies in autoimmune endocrine diseases was 41% and that these antibodies react mostly with an autoantigen weighing 68 kDa. Despite the number of studies conducted so far, only a few pituitary autoantigens responsible for the autoimmune processes have been identified.…”
Section: Discussionmentioning
confidence: 99%